Implementasi Metode PPP (Presentation, Practice, And Production) dalam Pembelajaran TOEFL Bagi Dosen di Universitas Nusa Tenggara Barat - Hilda, Hilda Hastuti; Erwin Suhendra; Puspita Dewi; Muhammad Zaki Pahrul Hadi (Insan Kreasi Media, 2022)
TOEFL training by implementing the Presentation, Practice and Production (PPP) method aims to help lecturers at the West Nusa Tenggara university in an effort to increase the TOEFL (Test of English as a foreign language) score. The difficulty of determining the right method and media to get the TOEFL score and score according to the cooled is the main reason for implementing this community service. This community service aims to provide not only knowledge but also readiness to face the TOEFL (Test of English as Foreign Language) exam for lecturers at the University of West Nusa Tenggara. The method used in this community service is the Presentation, Practice and Production (PPP) method. As the name implies, the PPP method prioritizes in-depth explanation of the material by the lecturer or tutor and then asks the service participants to practice working on questions and generate answers and analyzes from the participants. The results of this community service activity received a positive response from the partners, in this case the University of West Nusa Tenggara, especially because this program was in accordance with their needs. This form of positive response can be seen from the active participation, both from partners and from training participants. The motivation of the trainees to take part in the training process was quite enthusiastic. This indicates a desire to improve their ability to master the TOEFL in depth